40 A Study Of Bilateral Ultrasonographic Characteristics Of The Lateral Elbow Tendons In Unilateral Lateral Epicondylalgia. (5th September 2014) - Heales, Luke J; Hodges, Paul W; Vicenzino, Bill
Abstract : Introduction: Lateral epicondylalgia (LE) is associated with local tendon pathology in the common extensor tendon, as measured by musculoskeletal ultrasound imaging (MSUS)2. Recent studies have exposed tendinopathy-like changes in the tendon of the asymptomatic side of an animal model of repetitive unilateral exercise1 and a human model of unilateral Achilles tendinopathy3. It is compelling to hypothesise that there are tendinopathy-like changes in the asymptomatic common extensor tendon of people with unilateral LE. This prediction is strengthened by a recent systematic review with meta-analysis that identified sensory and motor system impairments in the asymptomatic limb of this group4. This study aimed to tests this hypothesis. Methods: Twenty-nine participants underwent a clinical examination to diagnose unilateral LE. Thirty-two controls without symptoms were matched for age, sex and arm dominance. Two sonographers who were blind to symptomatic side performed a MSUS examination, bilaterally, using a standardised protocol. Greyscale features and neovascularity were scored using separate ordinal scales that were used individually and summed to give a total greyscale, total neovascularity and aggregate overall. A repeated measures analysis of variance (ANOVA) was used to determine whether the individual and total scores from MSUS imaging differed between groups (LE vs. control) with the factor of side (dominant vs. non-dominant). Post hoc analysis was completed using Duncan's multiple range t-tests with significance set at p < 0.05. Results: The repeated measures ANOVA revealed a significant interaction (side x group p < 0.001) for greyscale score, neovascularity score and total score. Post hoc analysis revealed significantly more tendon abnormality in the dominant arm of the LE group than the matched arm of the controls (all p < 0.001). No significant differences were observed for any sonographic changes between the asymptomatic arm of the LE group and matched arm of the controls (all p > 0.05) (see Figure 1 ). The symptomatic tendon demonstrated significantly greater greyscale (mean difference 2.28, [95% CI 1.1–3.4], p < 0.001), neovascularity (1.53 [0.9 to 2.2], p < 0.001), and total (3.81, [2.3–5.3], p < 0.001) scores than the pain-free controls. Discussion: It appears that in unilateral LE, tendon pathology, as assessed by MSUS imaging, presents only in the symptomatic limb. This finding is inconsistent with that hypothesised from previous evidence of tendon changes in the asymptomatic side of people with Achilles tendinopathy. A possible explanation for the contrasting findings may be differences in methodology and/or populations. For instance, sonographers were not blind to group in earlier work, or differences in the anatomical location (and therefore pathophysiology) of the tendinopathy. Future studies are required that control for methodological issues and participant factors (e.g. systemic disease, physical activity level, etc), in unilateral LE and other tendinopathies. References: 1 Andersson, et al . BJSM . 2011;45:399–406 2 Clarke, et al . AJSM . 2010;38:1209–1214 3 Grigg, et al . MSSE . 2012;44:12–17 4 Heales, et al . BJSM . Online First 21 October 2013